Síndrome da encefalopatia reversível posterior: aspectos clínicos, imagenológicos e experimentais - Marrone, Luiz Carlos Porcello (2012)
INTRODUCTION : Posterior Reversible Encephalopathy Syndrome (PRES) is a clinico-radiological entity that presents with headache, altered mental status, seizure and visual disturbance and is associated with a reversible probably vasogenic edema, predominantly in occipital and parietal lobes. The precise physiopathology remains unclear and there isn t an experimental model of this disorder. OBJECTIVES : The objectives of this paper were (1) the clinical and radiological evaluation of patients with PRES in the Hospital São Lucas-PUCRS and (2) the development of a translational model based on clinical features that mimetize this syndrome in pregnants Wistar rats. METHODS : It was performed a review of clinical data, neuroimage and blood basic test of 25 patients with PRES, that were followed in Hospital São Lucas-PUCRS in the period from March 15 of 2007 to September 15 of 2011. Based on clinical features and neuroimagem findings, we developed a rat model of PRES using pregnant Wistar rats, which were submitted to a reduction of uterine pressure perfusion (RUPP), measurement of arterial blood pressure with an invasive catheter and a brain anatomo-pathologic study, after Evans s blue venous infusion to verify the permeability of the blood-brain-barrier. RESULTS : Our clinical sample consisted of 25 patients (4 men and 21 women) with mean age of 27,84 years old (range from 2 to 74 years old). The most common causes of PRES reported in this series were associated with pregnant situations that occurred in 11 cases (44%). The symptom more commonly reported was headache in 18 patients (72%). The occipital lobe was the most common topography of the magnetic ressonance abnormality (edema) and occurred in 23 cases (92%). The highest value of the systolic blood pressure presented the mean of 176 mmHg and the highest value of the diastolic blood pressure presented the mean of 95,2 mmHg. Animals submitted to RUPP to simulate the PRES presented increase of the blood-brain-barrier permeability and elevation of blood pressure, when compared with the control animals. CONCLUSION : In our series, PRES occurred predominantly in women and the most frequent triggers were obstetric causes; headache was the most common symptom and the neuroimage findings showed a predominance of posterior alteration suggesting a vasogenic edema due a breakdown of blood brain barrier. The experimental rat model was developed based on these clinical observations, so, we used pregnant rats submitted to reduction of uterine pressure perfusion. We identified in these animals increase of blood pressure and a breakdown of blood brain barrier corroborating to establish an experimental model of PRES. We believe that an experimental model of PRES could be important for future studies allowing a better comprehension of this syndrome.